Hepatic changes during a carrageenan induced granuloma in rats - J. Muntané; Y. Fernandez; S. Mitjavila; M. T. Mitjavila (Hindawi Limited, 1993)
Hepatic changes during inflammation were studied in rats bearing a carrageenan induced granuloma. In spite of a decrease in the metabolic capacity of microsomes to induce lipid peroxidation during inflammation, the endogenous lipid peroxidation remained unchanged and unrelated with the hepatic activities measured. The continuous increase in hepatic cAMP observed during acute and chronic phases could be related to adenylate cyclase stimulation by mediators, and could be an initial step in the hepatocyte adaptation leading to the increased level of hepatic caeruloplasmin, to the reduction of cytochrome P-450 level and to the modifications of Ca2+ sequestration by microsomes.